EFICACIA DE LOS PARAMETROS ANTROPOMETRICOS COMO PREDICTOR DE PERFIL DE RIESGOS CARDIOVASCULARES EN PERSONAS ADULTAS - Acosta González, Ysabel Dolores (2017)
Objective: to determine the efficacy among anthropometric parameters as predictors of cardiovascular risk in adults. Material and methods: systematic review are an observational and retrospective research design thet synthesizes the result of multiple primary investigations. They are an essential part of evidence-based nursing for its rigorous methodology, identifying relevant studies to aswer specific questions of clinical practice. Results: of the total ten articles analyzed, 90% stated that anthropometric parameters predict cardiovascular risk. These articles were found in the following databases pubmed, medline, elsevier, scielo and lilacs. Conclusions: anthropometric parameters predicted the existence of three or more cardivascular risk factors, both for adult men and adult women (high lipid profile, diabetes mellitus, hypertension, and smoking, among others).